2018
DOI: 10.1016/j.cell.2018.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Structural Remodeling of the Human Colonic Mesenchyme in Inflammatory Bowel Disease

Abstract: SummaryIntestinal mesenchymal cells play essential roles in epithelial homeostasis, matrix remodeling, immunity, and inflammation. But the extent of heterogeneity within the colonic mesenchyme in these processes remains unknown. Using unbiased single-cell profiling of over 16,500 colonic mesenchymal cells, we reveal four subsets of fibroblasts expressing divergent transcriptional regulators and functional pathways, in addition to pericytes and myofibroblasts. We identified a niche population located in proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
631
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(722 citation statements)
references
References 41 publications
60
631
1
Order By: Relevance
“…However, monolayers of UC, but not healthy gut MPSs, showed enlargement of hyperchromatic nuclei and irregular actin fragmentation, indicators of IBD dysplasia ( Fig.1E) (32). These morphological findings are consistent with observation that differentially-expressed genes ( Fig.1B,C) include those associated with regulation of actin, focal adhesions and cell junction, which are indicative of IBD-associated remodeling (33).…”
Section: Gut Mps Of Ulcerative Colitis Donor But Not Healthy Donorsupporting
confidence: 87%
“…However, monolayers of UC, but not healthy gut MPSs, showed enlargement of hyperchromatic nuclei and irregular actin fragmentation, indicators of IBD dysplasia ( Fig.1E) (32). These morphological findings are consistent with observation that differentially-expressed genes ( Fig.1B,C) include those associated with regulation of actin, focal adhesions and cell junction, which are indicative of IBD-associated remodeling (33).…”
Section: Gut Mps Of Ulcerative Colitis Donor But Not Healthy Donorsupporting
confidence: 87%
“…Using the previously described CellPhoneDB algorithm (Efremova et al, unpublished Vento-Tormo et al, 2018), we found that the three mesenchymal populations displaying the highest number of cell-type specific interactions with epithelial cell types were FOXL1+ and WNT4+ fibroblasts and UPK3B+ serosal cells ( Figure 4A). In our dataset, FOXL1+ fibroblasts expressed developmentally related genes such as DLL1 (Notch signaling ligand) and platelet derived growth factor receptor (PDGFR) (Karlsson et al, 2000;Kurahashi et al, 2008) as well as adult colonic mucosal S1 fibroblast markers including F3 and ADAMDEC1 (Kinchen et al, 2018). At 6 PCW, FOXL1 expressing fibroblasts were located in close proximity to the intestinal epithelium, as confirmed in situ using RNAscope ( Figure 4B).…”
Section: Cell-cell Cross-talk That Supports Crypt-villus Formation Insupporting
confidence: 63%
“…A second mechanism could be a zonated response to spatial gradients of nutrients and bacteria at the luminal sides of the tissue. Yet a third mechanism could entail zonated molecular cues that originate in the lamina propria, the underlying stroma at the basal sides of the epithelial layer [7][8][9][10] . Here, we use spatially-resolved transcriptomics to characterize the zonated stromal gene expression signatures along the crypt-villus axis.…”
Section: Introductionmentioning
confidence: 99%